MANAJEMEN BENCANA OLEH BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM MENANGGULANGI BANJIR DI KELURAHAN PEDURENAN KECAMATAN KARANG TENGAH KOTA TANGERANG - Baihaki, Muhamad; Khikmawanto, Khikmawanto; Arief, Muhammad (Gapenas Publisher, 2023)
Flood is a natural disaster that frequently occurs in coastal cities of Indonesia, and the government has a responsibility to mitigate its impacts through mitigation, emergency response, and post-disaster rehabilitation. The concept of disaster management, as described by W. Nick Carter, includes stages of prevention, mitigation, preparedness, disaster impact, response, recovery, and development. The National Disaster Management Agency (BNPB) was established by the government based on laws and presidential regulations, with local governments playing a significant role in disaster management according to applicable laws. In 2020, Tangerang City experienced significant flooding, especially in the districts of Karang Tengah and Pinang, resulting in thousands of families and individuals being affected and evacuated. The Tangerang City BPBD needs to have a strong response capacity and continually improve the capacity of human resources, institutions, infrastructure, and cooperation to deal with such situations. This research focuses on the efforts and hindering factors faced by the Tangerang City BPBD in handling the 2020 flood in the Pedurenan Sub-district, using qualitative research methods. The research results show the commitment of the Tangerang City BPBD in addressing the threat of flooding through proactive measures such as staff training, evacuation planning, and the KENCANA program, with a primary focus on strengthening infrastructure and community participation. The findings of this research are expected to serve as a basis for improving and developing policies and disaster management strategies in the future. In conclusion, the Tangerang City BPBD has taken significant steps to reduce flood risks and enhance community resilience through a holistic and proactive approach involving training, evacuation planning, infrastructure improvement, community participation, and inter-agency coordination. While progress has been made, there is still room for improvement to make flood disaster responses more effective in the future